2018
DOI: 10.1002/btpr.2666
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of phenotypic and genotypic diversity in subclones derived from a clonal cell line

Abstract: Regulatory guidelines require the sponsors to provide assurance of clonality of the production cell line, and when such evidence is not available, additional studies are typically required to further ensure consistent long‐term manufacturing of the product. One potential approach to provide such assurance of clonal derivation of a production cell line is to characterize subclones generated from the original cell line and assess their phenotypic and genotypic similarity with the hypothesis that cell lines deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 32 publications
1
28
1
Order By: Relevance
“…Over the last years, however, it has become increasingly clear that even clonally derived cell lines can gradually become genetically heterogeneous. Indeed, several studies have shown that subclones from the same cell line can display different phenotypic behaviors (Ko et al, 2018; Patel et al, 2018; Tharmalingam et al, 2018). In addition, clonally derived cell lines have been shown to display genetic evolution affecting their genome at various scales (from the accumulation of point mutations to chromosomal rearrangements), as well as epigenetic changes (Feichtinger et al, 2016; Vcelar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last years, however, it has become increasingly clear that even clonally derived cell lines can gradually become genetically heterogeneous. Indeed, several studies have shown that subclones from the same cell line can display different phenotypic behaviors (Ko et al, 2018; Patel et al, 2018; Tharmalingam et al, 2018). In addition, clonally derived cell lines have been shown to display genetic evolution affecting their genome at various scales (from the accumulation of point mutations to chromosomal rearrangements), as well as epigenetic changes (Feichtinger et al, 2016; Vcelar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…[10] On the other hand, several studies have brought into debate the relevance of clonality by reporting the appearance of differentiated expression patterns during the culture of cells derived from a clonal cell line. [11,12] Cell-to-cell differences have even been detected in master cell banks of CHO cells, but this heterogeneous cell population performed consistently in terms of product quality. [13] In the same line, the development of a clonal CHO cell line did not provide an improved homogeneity of future cell progeny.…”
mentioning
confidence: 99%
“…To select a cell line that will give high productivity, long‐term stability, and consistent product and process consistency, subcloning and extensive screening is required on hundreds of clonal cell lines, measuring growth, productivity and product quality in multiple screening assays (Wurm, ). In addition, regulatory agencies require that clinical trials be initiated with material from clonally derived cell lines and banks, so documentation that the cell line is derived from a single cell is required to provide that assurance of clonality (Tharmalingam et al, ).…”
Section: Development Of Cell Lines For Productionmentioning
confidence: 99%